Kualitas Proses Pembuatan Rencana Strategis (Renstra) Suatu Evaluasi Terhadap Peran Stakeholders di Kabupaten Lombok Barat - M. Nazarudin Fikri (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2001)
Together with reform initiatives and the new challenges in local development planning, the new ideas of strategic planning and strategic management are adopted to replace the old mechanisms of Rakorbang (Local Development Coordination) and Musbangdes (Village Development Forum) that were regarded as neglecting local participation. The local planning process under the Renstra (Perencanaan Strategis) is designed to involve local stakeholders, to be more participatory, and to be focused on equal partnerships. This study describes the process of Rensrra formulation in Lombok Barat municipality and aims to explain the role of local stakeholders in local development planning. It is found that the Renstra formulation process is still dominated by the ideas of local bureaucrats. The local government planning rends to be confined by Renstra manuals (Juklak and Juknis) that do not facilitate creativity and innovation. To some extent, the quality of Renstra is determined by whether it is formulated exclusively by the bureaucrats or involved wider interests of the legislatives, businessmen, or local NGOs. The most difficult phase of Rensrra formulation is the strategic issue formulation, which requires sophisticated analytical methods and accurate data. It is recommended that Renstra process should be started from the grassroot participation, which means that it needs a extensive participation of the newly established village councils.